The congenital cataract-linked A2V mutation impairs tetramer formation and promotes aggregation of βB2-crystallin. - Jia Xu (Public Library of Science (PLoS), 2012)
β/γ-Crystallins, the major structural proteins in human lens, are highly conserved in their tertiary structures but distinct in the quaternary structures. The N- and C-terminal extensions have been proposed to play a crucial role in mediating the size of β-crystallin assembly. In this research, we investigated the molecular mechanism underlying the congenital hereditary cataract caused by the recently characterized A2V mutation in βB2-crystallin. Spectroscopic experiments indicated that the mutation did not affect the secondary and tertiary structures of βB2-crystallin. The mutation did not affect the formation of βB2/βA3-crystallin heteromer as well as the stability and folding of the heteromer, suggesting that the mutation might not interfere with the protein interacting network in the lens. However, the tetramerization of βB2-crystallin at high protein concentrations was retarded by the A2V mutation. The mutation slightly decreased the thermal stability and promoted the thermal aggregation of βB2-crystallin. Although it did not influence the stability of βB2-crystallin against denaturation induced by chemical denaturants and UV irradiation, the A2V mutant was more prone to be trapped in the off-pathway aggregation process during kinetic refolding. Our results suggested that the A2V mutation might lead to injury of lens optical properties by decreasing βB2-crystallin stability against heat treatment and by impairing βB2-crystallin assembly into high-order homo-oligomers.